PENYULUHAN PENGENDALIAN HAMA DAN PENYAKIT TERPADU PADA TANAMAN JAGUNG DI DESA URSANA, KECAMATAN INAMOSOL - Patty, John Alfred (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2025)
The demand for corn plants continues to increase from year to year, but the production results have not been able to meet the needs of the community due to low harvests. Pests and diseases of corn plants are one of the main causes of low corn harvests. This community service activity aims to provide practical knowledge and skills to the community about the introduction of types of pests and diseases of corn plants. The target of this activity is the community of Ursana Village, Inamosol District, West Seram Regency. Community participation in this activity is very good related to the problems faced by farmers, namely the main pests and diseases of corn plants that cause losses, in terms of quantity and quality. Positive responses from extension participants to continue effective and efficient control techniques, in order to minimize control costs and increase farmer knowledge in corn cultivation efforts. Therefore, farmers really need information related to the types of pests and main diseases of corn plants and their control techniques.